PENGARUH ORANG TUA, PENGETAHUAN KEUANGAN DAN GAYA HIDUP DALAM POLA PENGAMBILAN KEPUTUSAN FINANSIAL MAHASISWA - Lioni Indrayani; Wisjnumurti B Permadi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
College student represent young adult who are well educated especially comes to financial considerations. In daily basis, students need to make financial decisions in quick and accurate manner. One of them is about saving. Saving is known as an attitude as to how important future to most people. Saving is an action of keeping a part of income for future consumption. People have their own motives for saving their money. It is also believed that those motives are influenced by several things such as home education, school education and personal life-style. We are interested to study those motives, how they influences saving behaviour. We distributed questioners to University of Pamulang students and had received 100 answers which then we summarized and studied the results so we can have a good understanding on motives that influence on saving behaviour.